2022
DOI: 10.1111/srt.13150
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach to detect blood vessels in basal cell carcinoma

Abstract: Purpose: Blood vessels called telangiectasia are visible in skin lesions with the aid of dermoscopy. Telangiectasia are a pivotal identifying feature of basal cell carcinoma.These vessels appear thready, serpiginous, and may also appear arborizing, that is, wide vessels branch into successively thinner vessels. Due to these intricacies, their detection is not an easy task, neither with manual annotation nor with computerized techniques. In this study, we automate the segmentation of telangiectasia in dermoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Twelve articles reported on the detection of BCC in dermoscopy images 30‐41 . Half of the studies included used retrospectively collected datasets, such as ISIC‐2018 and ISIC‐2019, which contain multiple skin conditions including malignant lesions such as BCC and benign conditions 42,43 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve articles reported on the detection of BCC in dermoscopy images 30‐41 . Half of the studies included used retrospectively collected datasets, such as ISIC‐2018 and ISIC‐2019, which contain multiple skin conditions including malignant lesions such as BCC and benign conditions 42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Two articles reported on the accuracy for multiple classes; hence, we calculated sensitivity and specificity from the provided confusion matrix (Table 1). 30,31 The accuracy (for binary outcome) was reported in one study, 37 while one study 39 reported the detection rate as the main outcome. Two studies 32,34 developed a binary classier (BCC vs no‐BCC) using relatively comparable data set sizes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning (ML) methods have recently been investigated in the field of dermatology, and the majority of developed algorithms are diagnostic binary classifiers [11,12]. A number of studies have evaluated the performance of algorithms developed to detect specific dermoscopic features, including pigment network structures, vessels, and blue-white veil; however, many algorithms were trained and tested on relatively small data sets and have achieved only moderate accuracy [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%